Effectiveness of Ipomoea Aqua Forsk in Phosphate Absorption and pH Neutralization of Detergent Wastewater - Herdianti Herdianti; Elsusi Martha; Novela Sari; Hengky Oktarizal; Sa'diah Erlina; Firdaus Yustisia Sembiring (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
One of the causes of environmental pollution is the direct disposal of wastewater into the environment. Disposal of wastewater both originating from domestic (household) and industrial activities into water bodies can cause environmental pollution. As one example, namely laundry waste that is discharged directly into water bodies. The high phosphate content in the laundry waste causing an algae boom and can reduce dissolved oxygen content so that it will result in the death of aquatic biota. The purpose of this study was to find out the optimization Phosphate absorption and pH neutralization of laundry wastewater using Ipomoea sp (Ipomoea Aqua Forsk) in Batam City. This research is an Experimental study with a One Group Pretest-Posttest Design design. Waste samples were taken in one of the laundry businesses located in kel. Sadai, kec. Confused. The subject of this research is the Ipomoea sp., and the object of this research is the level of phosphate and pH contained in laundry wastewater. The results of the treatment that the researchers carried out in treatment I obtained the optimal weight was 500gr of Ipomoea sp growth and could reduce phosphate levels to 0.13 mg/L, and pH to 8.10 pH units, while in treatment II the optimal length of time was 6 days to be able to lowered the phosphate level to 0.09 mg/L, and the pH to 7.60 pH units. The conclusion of this study is that the optimal weight of Ipomoea sp. is 500 grams and the optimal length of time is 6 days. Suggestions from this study are, laundry business owners and the surrounding community are encouraged to Ipomoea sp along the ditches through which laundry waste water passes.Keywords: Ipomea Sp, Laundry, Phosphate, Ph, Wastewater